Elaboração e caracterização de filmes coacervados à base de gelatina/quitosana, gelatina/pectina e gelatina/goma arábica - Braga, Andréa Helena Ferreira, 1980- (2013)
Orientador: Carlos Raimundo Ferreira Grosso